The human vaginal microbial community dysbiosis contributes to the urinary tract infections during pregnancy: Case study of Gisenyi District Hospital, Rwanda - Yadufashije, Callixte; Muhimpundu, Liliane; Munyeshyaka, Emmanuel; Mucumbitsi, Joseph (Asian Journal of Medical Sciences, 2021)
Background: Urinary tract Infections (UTIs) are the common infections during pregnancy. About 150 million UTIs occur every year globally, and 30% is attributed to pregnant women. Aims and Objective: The study was carried out to observe the association with vaginal microbial community imbalance and urinary tract infections among pregnant women. Materials and Methods: A total of 80 pregnant women were recruited. Of the 80 women, 40 were pregnant with UTI, and the remaining 40 were women without UTI. About 80 vaginal swab samples were collected and transported to INES clinical microbiology laboratory for microbiological analysis. Laboratory techniques including culture, gram stain, and biochemical tests were performed. ANOVA-2 was used for comparison, while chi square (χ2) was used to test for association. Results: E. coli was predominant among women with UTIs while Lactobacilli predominated among women without UTIs. There was a statistical significance association with vaginal microbial community imbalance and urinary tract infection among pregnant women to Escherichia coli (χ2=9.97, p=0.0015), Staphylococcus epidermidis (χ2=5.12, p=0.023), Proteus spp (χ2=4.96, P=0.025), Citrobacter spp (χ2=32.51, P<0.00001), Streptococcus pyogenes (χ2=5.11, P=0.023), Staphylococcus sapropyticus (χ2=4.3, p=0.038) and Lactobacilli species (χ2=13.7, p=0.00021). The overall association (χ2=94.879, p<0.00001) with all isolated microorganisms and urinary tract infections was statistically significant. The odd ratio of pathogenic microorganisms to non-pathogenic was OR=4.98>1. For ANOVA-2, there was a higher microbial variation or differences among women with UTIs (F=7.241842) compared to women without UTIs (F= 4.71 ) in pregnancy trimesters. Conclusion: Pregnancy is associated with vaginal microbial community imbalances which predispose women to urinary tract infections. Pregnant women should seek for medical assistance during pregnancy for early detection of urinary tract infections.